An Iron-Based Catalyst with Multiple Active Components Synergetically Improved Electrochemical Performance for Oxygen Reduction Reaction - Jian Zhang (Catalysts, 2018)
Lack of highly active and stable non-precious metal catalysts (NPMCs) as an alternative to Pt for oxygen reduction reaction (ORR) in the application of zinc-air batteries and proton-exchange membrane fuel cells (PEMFCs) significantly hinders the commercialization of these energy devices. Herein, we synthesize a new type of catalyst composed of nitrogen-coordinated and carbon-embedded metal (Fe-N/Fe3C/Fe/C) by pyrolyzing a precursor at 800 °C under argon atmosphere, and the precursor is obtained by heating a mixture of the tri (dipyrido [3,2-a:2′,3′-c] phenazinyl) phenylene and FeSO4 at 160 °C in a Teflon-lined stainless autoclave. The resultant Fe-N/Fe3C/Fe/C-800 exhibits the highest activity for the ORR with onset and half-wave potentials of 1.00 and 0.82 V in 0.1 M KOH, respectively. Furthermore, it also shows a potential ORR activity in 0.1 M HClO4, which is promising for the application in commercial PEMFCs. Most importantly, Fe-N/Fe3C/Fe/C-800 exhibits a comparable electrochemical performance to Pt/C for the application in zinc-air battery. The specific capacity approaches 700 mAh·g−1, and the maximum power density is also comparable to that of Pt/C at the current density of 200 mA·cm−2. The work opens up a simple strategy to prepare ORR electrocatalyts for zinc-air battery and PEMFCs.